Current practice of airway stenting in the adult population in Europe: a survey of the European Association of Bronchology and Interventional Pulmonology (EABIP) - Dutau, Hervé; Eberhardt, Ralf; Herth, Felix (Respiration, 2017)
Background: Airway stenting (AS) commenced in Europe circa 1987 with the first placement of a dedicated silicone airway stent. Subsequently, over the last 3 decades, AS was spread throughout Europe, using different insertion techniques and different types of stents. Objectives: This study is an international survey conducted by the European Association of Bronchology and Interventional Pulmonology (EABIP) focusing on AS practice within 26 European countries. Methods: A questionnaire was sent to all EABIP National Delegates in February 2015. National delegates were responsible for obtaining precise and objective data regarding the current AS practice in their country. The deadline for data collection was February 2016. Results: France, Germany, and the UK are the 3 leading countries in terms of number of centres performing AS. These 3 nations represent the highest ranked nations within Europe in terms of gross national income. Overall, pulmonologists perform AS exclusively in 5 countries and predominately in 12. AS is performed almost exclusively in public hospitals. AS performed under general anaesthesia is the rule for the majority of institutions, and local anaesthesia is an alternative in 9 countries. Rigid bronchoscopy techniques are predominant in 20 countries. Amongst commercially available stents, both Dumon and Ultraflex are by far the most commonly deployed. Finally, 11 countries reported that AS is an economically viable activity, while 10 claimed that it is not. Conclusion: This EABIP survey demonstrates that there is significant heterogeneity in AS practice within Europe. Therapeutic bronchoscopy training and economic issues/reimbursement for procedures are likely to be the primary reasons explaining these findings.
Gesehen am 05.07.2019